(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2010)
The present article considers the ore field with profile porphyrу-molybdenum-copper industrial mineralization. Its developed combined geological-structural, geophysical and ore-geochemical model expressed in the graphic form has allowed to clarify a number of questions: to define the position of polytypic mineralization in gravimetric anomalies, the horizontal and vertical zonality of the mineralization, the perspective sites with copper and gold mineralization, accompanying porphyry molybdenum-copper and to predict data on its depth.